Asylum Amidst Crisis: The Evolution of Poland’s Refugee Legislation in the Wake of the Ukrainian Exodus (TEST Trento Student Law Review, 2025)
The article examines Poland’s legislative response to the sudden influx of Ukrainian refugees, caused by the Russian invasion of the country, with a focus on the Special Act as an implementative tool of the Temporary Protection Directive. Through a longitudinal analysis, it analyzes the way in which the Polish legal framework adapted to said sudden arrival of refugees, with particular attention to mechanisms such as access to employment, social support, and broader integration. The overall aim of the work, by using a doctrinal legal analysis of both national legislation and EU directives, is to evaluate the effectiveness and limitations of the dual protection established by the Polish Special Act. While this latter provided rapid solutions to the crisis, it also revealed both structural gaps in long-term integration and a systematic deservingness-based approach in the acceptance and inclusion of migrants coming into the State territory.
Keywords: Protection; Poland; Ukraine; Temporary Protection; Refugee Crisis